The Speech Diction of the Tamil language in ‘MAHAIYAVA’ village: A Linguistic Analysis of Sinhala and Tamil Language - Sunil Wickrmasinghe, L.A. (University of Peradeniya, 2014)
Mahaiyawa is a rural community in Sri Lanka. It is located within Central Province 02km away form kandy city. It is a place with a very little people in the province of Central, Sri Lanka. In Mahaiyava lots of Sinhalese verbalize Tamil words apart from foreigners. This movement is mainly understandable in the middle of the younger age group. In point, this language selection tends to put back their racial or community language. In the recent globalized world the English language has turn into a language phenomenon which forces to people for use it. But many Sinhalese speck Tamil without any English expressions. This subject is central for quite a few reasons. Primary, the utilize of non English languages at home town has enlarged radically more the past few decades due to concentrated cultural immigration from other Sinhala villages such as ‘Asgiriya, Hanthana, Kaunasale and Digna’. On this individual level, debate has centered on the potential costs and profits of bilingualism in young children. The argument surrounding bilingualism is exaggerated by an intellect of urgency generated by the changing demographic picture. The purpose of this article is to present the speech diction of Tamil language which Mahiyava people verbalize. How their language ability contact with another influence? Why they use multidimensions? Resolve those questions I have collected data by observation frame work including library contribution.
Keywords: Agency; Demographic; Bilingualism; Cultural immigration